Efficiency Assessment of Coordinated Hierarchical Dynamic Spectrum Management for Mobile Ad Hoc Networks - Jerzy LOPATKA1; Jerzy DOLOWSKI1; Rafal BRYS2; Boguslaw GROCHOWINA2 (Communications of International Proceedings, 2021)
The aim of this study is to assess the efficiency of hierarchical management of dynamic spectrum access for mobile ad ’hoc networks, to improve the performance of the network in presence of interference and jamming. The simulations are preformed using MAENA network simulator. Next, analysis of the results for the selected test scenario are presented.
Keywords: MANET; resistance to interferences; Dynamic Spectrum Management.